(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2023)
The purpose of this article is to examine primordial issues in electoral political contestation in a plural Indonesian society. Electoral political contestation became a breeding ground for primordial issues. The majority wants to be led by a leader who is of the majority religion. Religious and tribal issues are used to win political contests. Indigenous and pagan narratives are echoed and lead to division. This aticle uses qualitative methodology with a leterer study approach referring to Emmauel Levinas’ ethical theory of responsibility for analyzing data. The levinian ethic of responsibility expresses the idea of placing others as unique and different subjects altogether through their visible faces. The consequence is that the other must be respected and valued as subjects. At the same time the presence of others becomes the responsibility of "me", not absorbing others to equate with myself or even subjugate or master. Data is obtained from internet searches such as news and surveys conducted by LSI (Indonesian Survey Institute). This article finds that the understanding of politics is reduced only to the understanding of electoral political contestation alone. Poltik lost its meaning as a form of living together to achieve the common good (Bonum Commune). The article proposes that Indonesian education incorporate political education into the national education curriculum and multicultural education is further emphasized in schools so that primordial issues do not develop rapidly, and future generations can accept Indonesia’s plural reality.